The Birds: Afterimages; After Hitchcock (2nd Attempt) - Miguel Mesquita Duarte (Screenworks)
By using digital manipulation as the primary method of experimentation and transformation of the very fabric of The Bird's original images, rather than just its narrative structure and sequence, this piece extends beyond the level of critique and representation to consider the composition of the image, its legibility as an image and the potential historical significance of this new legibility. It explores the visual boundary between the plausible and the unimaginable dimensions of reality, transforming the camera into a dehumanized gaze. This shift serves as a metaphor for perceiving the intolerable, the unbearable, signaling an altered perception of the original film. Ultimately, the piece consubstantiates the materialization of a de-anthropomorphized, off-screen space within the image itself, potentially enabling the articulation of content and form, the familiar and the unfamiliar, technological visibility and invisibility.